(untitled) (Geographical Journal of Nepal, 2020)
Rapid transformation of rural settlements into municipalities in Nepal has brought significant changes in land use and urban expansion patterns mostly through the conversion of agriculture land into the built up area. The issue is studied taking a case of rapidly growing Tarai town of Bedkot Municipality of Kanchanpur District. This study is based on field interaction, observation, and available data review. After the declaration of Bedkot as a municipality, several new roads have been opened and upgraded; and the municipality is well connected to the national transportation network. After promulgated the Constitution of Nepal, 2015 and activated the elected local body, the municipality budget has been increased significantly as a result of increasing municipal investment on socio-economic and physical infrastructure development and environmental protection which have attracted people, goods and services creating it as the zone of influence of the surroundings. Rapid spatial changes have been observed with inflow of population in the municipality. One of the changes found is the increasing built-up area by 3.6 percent and expansion of urban area through decreasing the agriculture land by 3.5 percent. Urban growth has been observed taking place along the highway corridor clustering at nodal junctions and some other potential locations. Implications of such spatial dimensions have been core issue of urban development planning in most of the newly declared municipalities in Nepal.